(untitled) (Research Nepal Journal of Development Studies, 2018)
Extreme poverty, illiteracy, unemployment, poor law enforcement, and open border between India and Nepal are major factors for human trafficking. Due to the devastating earthquake that hit Nepal on April 25, 2015, which was followed by more than 400 aftershocks, about 3 million people were victimized. The earthquake victims- women and children, were more vulnerable to trafficking than before. Hence, it is vital to understand human trafficking, its form, factors, effects, and motives. The objective of this paper is to make intellectuals aware of the issue of sex trafficking, problems, and possible solutions in Nepal. Research Nepal Journal of Development Studies Vol.1(1) 2018 28-31